Analisis Dan Perancangan Sistem Informasi Pemasangan Jaringan Listrik Baru Pada PT. PLN (Persero) Area Pelayanan Sepatan - Tjahjono, Budi (JIK: Jurnal Ilmu Komputer, 2008)
New electricity network installing information system in PT. PLN area service sepatan registration information data customer transaction stills too complex and need many paper medias for the presentation, sometimes also livelihood time process information very slow and consume many times. This system genuinely still done according to manual, so that when does data or information hits customer transaction is difficult insides to be founded. Analysis and system planning that made to use model of unified modelling language and system that built to use visual programming language basic 6.0 based on microsoft access.Keywords: Analysis, Planning, Information System